Structural state study of high-purity titanium after severe plastic deformation and cryogenic quasi-hydrostatic extrusion by XRD methods - Boklag, E.E.; Kolodiy, І.V.; Tikhonovsky, M.A.; Kislyak, I.F.; Khaimovich, P.A.; Efimov, A.A. (Вопросы атомной науки и техники, 2015)
Nanocrystalline bulk high-purity titanium samples were obtained by combined severe plastic deformation SPD, thermal treatment and quasi-hydrostatic extrusion QHE at liquid nitrogen LNT and room RT temperatures. Texture and microstructural evolution of Ti have been investigated by XRD methods. The effect of initial structural state on deformation behavior of Ti after QHE was established. QHE of ultrafine-grained samples leads to structure formation, which parameters are independent on temperature of QHE. Significant differences in QHE process are observed for pre-annealed coarse-grained samples. These differences are related to deformation mechanisms, activated during the QHE process at LNT and RT. Методами комбинированной интенсивной пластической деформации, термообработок и квазигидроэкструзии (КГЭ) при азотной и комнатной температурах получены объемные нанокристаллические образцы высокочистого титана. Исследования текстуры и микроструктурных параметров титана проводились методами рентгеновской дифрактометрии. Установлено влияние исходного структурного состояния образцов на деформационное поведение титана при КГЭ. КГЭ ультрамелкозернистых образцов приводит к формированию структуры, параметры которой практически не зависят от температуры КГЭ. Значительные отличия наблюдаются в случае предварительно отожженных крупнозернистых образцов. Это связано с различными механизмами деформации (скольжением дислокаций и двойникованием), которые активируются в процессе КГЭ при комнатной и азотной температурах. Методами комбінованої інтенсивної пластичної деформації, термообробок та квазігідроекструзії (КГЕ) при азотній та кімнатній температурах отримано нанокристалічні об’ємні зразки високочистого титану. Дослідження текстури та мікроструктури титану проводилися методами рентгенівської дифракції. Встановлено вплив початкового структурного стану зразків на деформаційну поведінку титану при КГЕ. КГЕ ультрадрібнозернистих зразків призводить до формування структури з параметрами, незалежними від температури КГЕ. Значні відмінності спостерігаються у випадку попередньо відпалених крупнозернистих зразків. Це пов’язано з різними механізмами деформації (ковзанням дислокацій та двійнікуванням), що активуються під час КГЕ при кімнатній та азотній температурах.